The Relationship Between Giving Pilis (Rice, Turmeric, Sand Ginger, Ginger, Lime) and Postpartum Maternal Health - Annah Hubaedah (EMBRIO: Jurnal Kebidanan, 2024)
The use of traditional herbs is intended for postpartum health care and recovery. To see the benefits of using these ingredients, it is necessary to study the relationship between the provision of traditional ingredients and the health impacts on postpartum mothers who use them. This study aims to determine the relationship between giving pilis (rice, turmeric, sand ginger, ginger, lime) and the health of post-partum mothers. This type of quantitative research uses a correlational analytical research design using a cross-sectional approach. The sample in this study was 43 postpartum mothers in the ten public health centers of the Bangkalan Madura district. The data collection technique uses an observation sheet instrument. Sampling used simple random sampling nonparametric statistical analysis with analysis tests using Chi-Square. The research results showed a relationship between giving pilis (rice, turmeric, sand ginger, ginger, lime) and the health of post-partum mothers, as evidenced by a p-value of 0.000 less than 0.05. In conclusion, giving pilis to postpartum mothers continues to be maintained because of its perceived health benefits, which are in line with the expectations of the Bangkalan community. Suggestion: The development of traditional medicine from a pharmacological perspective must be carried out so that people can use traditional medicine according to standards. After development by pharmacologists, a postpartum mother treatment policy based on local, family, and community wisdom can be formulated.